Mapping 216 Perforator Flaps Using Highly Portable Tablet-Based Color Doppler Ultrasound (PT-CDU) - Lindsey, John T., Jr; Smith, Christopher; Lee, James; St Hilaire, Hugo; Lindsey, John T., Sr (Journal of Reconstructive Microsurgery, 2021)
Background The first reports of using color Doppler ultrasound for evaluation of the microvasculature were in the 1990s. Despite the early reports of its efficacy, color Doppler ultrasound did not achieve popularity nor general usage in part due to the cumbersome size, cost and poor resolution. This is the first study to demonstrate the potential utility of a new, highly portable, tablet-based color Doppler ultrasound (PT-CDU) system for imaging perforator flaps.Methods The deep inferior epigastric artery (DIEP), lateral arm (LA), anterolateral thigh (ALT), thoracodorsal artery (TDAP), and the medial sural artery (MSAP) perforator flaps were imaged within classic topographic landmarks to visualize and measure variables related to perforator flap anatomy. The Philips Lumify L12–4 linear array probe attached to the Samsung Galaxy Tab A tablet was the system used for all examinations.Results A total of 216 flaps were scanned in 50 healthy adult volunteers: 44 DIEP, 44 LA, 40 ALT, 48 TDAP, and 40 MSAP. Precise anatomic information regarding perforator size, number, and location was obtained. Overall, the percent of flaps having at least 1 perforator within the specified topographical landmarks was 89% for the DIEP, 84.1% for the LA, 72.5% for the ALT, 50% for the TDAP, and 30% for the MSAP (p = 2.272e-09). The percent of patients having an asymmetry (right versus left) in the number of perforators was 72.7% (ALT), 65% (DIEP), 59.1% (LA), 41.7% (TDAP), and 30% (MSAP) (p = 0.0351).Conclusion Portable, tablet-based color Doppler ultrasound offers high-resolution images of perforators and represents a facile technology that may be of interest to microsurgeons in the planning of perforator flaps. Variations in vascular anatomy were well-demonstrated. This surgeon-driven imaging technology may represent an excellent alternative to other imaging modalities.
Keywords: color doppler; perforator flaps; preoperative imaging